1998
DOI: 10.1023/a:1022341909396
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to further investigate the potential of rifamycins as antiinflammatory drugs, twenty-five semisynthetic rifamycins were tested at concentrations ranging from 10(-9) to 10(-5) M on in vitro human neutrophil functions such as locomotion, superoxide anion production, and degranulation, under different stimulatory conditions. They were also tested as antiproliferative agents on peripheral blood lymphocytes. The present semisynthetic derivatives are in general characterized by their carrying a hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Drugs belonging to the rifamycin class exert anti-inflammatory activity, which seems to be independent from the anti-microbial properties. Rifamycins indeed inhibit human neutrophil functions ( Spisani et al, 1997 , 1998 ) and intra-articular rifamycin SV was shown to be effective in patients with chronic arthritides, like juvenile rheumatoid arthritis and ankylosing spondylitis ( Caruso, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drugs belonging to the rifamycin class exert anti-inflammatory activity, which seems to be independent from the anti-microbial properties. Rifamycins indeed inhibit human neutrophil functions ( Spisani et al, 1997 , 1998 ) and intra-articular rifamycin SV was shown to be effective in patients with chronic arthritides, like juvenile rheumatoid arthritis and ankylosing spondylitis ( Caruso, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that rifamycins inhibit human neutrophil functions and may therefore display an anti-inflammatory action [93, 94]. And indeed, intra-articular rifamycin has been successfully used in chronic arthritides, like juvenile rheumatoid arthritis and ankylosing spondylitis [95].…”
Section: General Pharmacologymentioning
confidence: 99%
“…[26][27][28] In addition, rifamycin SV has a strong inhibitory effect on polymerase enzymes. 29) A few studies have investigated effects of some medical drugs on human serum PON1 enzyme in vitro. Most of these, on the modulation of PON1 by pharmaceutical compounds, have focused on lipid-lowering compounds.…”
Section: Resultsmentioning
confidence: 99%